Using literature to enhance writing instruction a guide for K-5 teachers - Olness, Rebecca (International Reading Association, 2005)
"Rebecca Olness combines her love of children?s literature and her experience as a classroom teacher and literacy specialist to show how to teach content and literacy concepts simultaneously."--Publisher's description.